Blood transfusion practices in obstetrics and gynecology: study of indications as a measure to prevent maternal morbidity and mortality - Chaudhary, Neeta; Tyagi, Natasha; Tyagi, Smita; Manchanda, G. S.; ., Malvika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This is a study of rational use of blood transfusion in a tertiary care center. So, this study was done to find out the indications of blood transfusion in department of obstetrics and gynaecology and measures to minimize the requirement of blood transfusion to reduce maternal mortality and morbidity. Methods: This is a retrospective study in department of obstetrics and gynaecologyin Muzaffarnagar Medical College, Muzaffarnagar, U.P. in collaboration with the department of pathology including blood bank for the duration of 1 year i.e. 1st January, 2017 to 31st December, 2017. Total transfusions in 1 year were 706 of which 406 were in obstetrics and 300 were in gynecology. Results: In our study maximum 16.20% blood transfusions were given during cesarean section in third trimester in unbooked cases who came with severe anemia in labour. Others were APH (12%) and abortions (13.05%). This shows that anemia is still a major cause of maternal mortality and morbidity in India. In Gynecological cases blood transfusion was more in third parity and above indicating that perimenopausal women were also more susceptible for anemia due to disease of perimenopausal age group like AUB and fibroid. Conclusions: Maximum number of transfusions specially PRBC in obstetrics were of moderate to severe anemia, mainly to the patients who were term or in labor and of high-risk pregnancies, who were unbooked with no antenatal care. In Gynecology cases, blood transfusion was of perimenopausal or menopausal group with moderate anemia. This comes to the conclusion that all preventive measures should be taken in females from womb to tomb to correct anemia and this will indirectly help to prevent maternal and perinatal morbidity and mortality.